PARTISIPASI MASYARAKAT DALAM MEWUJUDKAN KAMPUNG WARNA-WARNI TELUK SERIBU KOTA BALIKPAPAN (Community Participation In The Development Of Kampung Warna-warni Teluk Seribu In Balikpapan City) - Mahagarmitha, Rilia Rigina (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, Kupang, 2018)
The growth and development of the city is one of driving factors for the emergence of slums in urban areas. Slums are usually located on the outskirts of the city, an example of which can be found in Balikpapan known as “Kampung Nelayan” slum area. A common condition takes place in other big cities in Indonesia, and this has led the government to formulate programs and policies by issuing government regulations Undang-undang Nomor 1 Tahun 2011 concerning to Housing and Human Settlement Areas. It is stipulated in the regulation that “The management of slums must be carried out by the central Government, local Government and/ or by every individuals”. To improve the welfare and a better life quality, active community participation is needed to build sustainable habitable human settlements. In order to explore more about this concept, a research was conducted at Kampung Nelayan Warna-warni Teluk Seribu. The research aims at learning more about the roles of the community and obstacles encountered in developing Kampung Nelayan Warna-warni Teluk Seribu. The method used is descriptive analysis through observation, interview, literatures study, and related documents. The result of the research shows that community participation plays a successful role in developing Kampung Nelayan Warna-warni Teluk Seribu as one of the tourist attractions in Balikpapan which, then, leads to economic enhancement of local community and Balikpapan city. Keywords: slums, community participation, sustainable